Antihyperlipidemic and antioxidant capacities, nutritional analysis and uhplc-pda-ms characterization of cocona fruits (Solanum sessiliflorum dunal) from the peruvian amazon - Vargas-arana G. (2021)
Funding: This research was funded by the Project Concytec – Banco Mundial “Mejoramiento y Ampliación de los Servicios del Sistema Nacional de Ciencia Tecnología e Innovación Tecnológica” 8682, through its executing unit Fondecyt [Contrato N° 119-2018-FONDECYT-BM-IADT-MU]. M. J. S acknowledge fondecyt 1180059.